YEASTS MACROSCOPIC FUNGI LICHENS AND HEPATICAE FROM CUICATLAN OAXACA - RUIZ ORONOZ, MANUEL; HERRERA, T (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1964)
Twenty-one spp of algae belonging to the Myxophyceae, Desmidiaceae, Chlorophyceae and Chladophoraceae are descr and figured
ANS INST BIOL
Keywords: YEASTS, MACROSCOPIC FUNGI, LICHENS, HEPATICAE, CUICATLAN, OAXACA; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL